Evaluation Of The Internal Control System Of The Balance Sheet At The Pelmas Cooperative, Faomasi Lahewa Group - Noniar Juni Artati Zebua; Noviza Asni Waruwu; Kurniawan Sarototonafo Zai; Dedi Irawan Zebua (Universitas Dehasen Bengkulu, 2026)
This study is motivated by the fact that the internal control system in cooperatives still faces several challenges. The problems identified include the absence of a written Standard Operating Procedure (SOP) as a work guideline, financial reports that remain difficult for some members to understand, and the use of a relatively simple risk analysis method. These conditions potentially reduce the effectiveness of control, the reliability of financial reporting, and the transparency of the cooperative. The purpose of this study is to evaluate the implementation of the internal control system in the preparation of the balance sheet of PELMAS Cooperative, Faomasi Lahewa Group, based on the COSO 2013 framework.This research employs a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation. The study involved six informants consisting of cooperative managers, supervisors, and members. Data analysis was conducted using source triangulation to obtain valid and comprehensive results.The findings indicate that, in general, the implementation of internal control has been carried out fairly well, as evidenced by a clear division of tasks, routine financial audits, transparent reporting, and the regular implementation of the Annual Members’ Meeting (RAT). However, some weaknesses remain, such as the absence of written SOPs, limited member understanding of financial reports, and the suboptimal application of risk analysis.The conclusion of this study is that the cooperative has applied the COSO 2013 components in a simple yet not fully optimal manner. Therefore, it is recommended that the management immediately develop written SOPs, enhance the capacity of managers and members through training, and present financial reports in a simpler and more comprehensible comprehensibleformatforallmembers.